A Novel Method for Polyacrylamide Gel Preparation Using N-hydroxysuccinimide-acrylamide Ester to Study Cell-Extracellular Matrix Mechanical Interactions - Kumai, Jun; Sasagawa, Satoru; Horie, Masanobu; Yui, Yoshihiro (Frontiers in Materials, 2021)
Mechanical stimulation by the extracellular matrix (ECM) controls physiological and pathological cellular responses, such as stem cell differentiation, organogenesis, and tumor progression. Polyacrylamide (PA) gels have been widely used to study cell-ECM mechanical interactions. Typically, sulfosuccinimidyl 6-(4′-azido-2′-nitrophenylamino)hexanoate (sulfo-SANPAH) is used as a protein crosslinker in these gels. However, its low solubility, unstable binding with proteins, and high cost are barriers to its application. The objective of this study was to improve and simplify the preparation of PA gels using an economical crosslinker, N-hydroxysuccinimide-acrylamide (NHS-AA) ester, to enable increased stability in protein coating. By exposing excess NHS to the gel surface, we found an optimal ratio of NHS-AA ester:AA to obtain NHS-AA ester-containing PA gels with a uniform protein coating and similar stiffness as that of sulfo-SANPAH-containing PA gels. The biological behavior of MCF7 and MCF10A cells were similar on NHS-AA ester and sulfo-SANPAH gels. Acini formation in Matrigel overlay culture were also consistent on NHS-AA ester and sulfo-SANPAH gels. This novel PA gel preparation method using NHS-AA ester can effectively replace the sulfo-SANPAH method and will be tremendously useful in the evaluation of cell-ECM mechanical interactions.